A transdiagnostic model of psychiatric symptom co‐occurrence and autism spectrum disorder. Issue 4 (24th October 2019) - Rodriguez‐Seijas, Craig; Gadow, Kenneth D.; Rosen, Tamara E.; Kim, Hyunsik; Lerner, Matthew D.; Eaton, Nicholas R.
Abstract : Understanding whether the co‐occurrence of psychiatric symptoms within autism spectrum disorder (ASD) are specific to the ASD diagnosis or reflect similar higher‐order patterns observed in both ASD and non‐ASD samples, or a confluence of the two, is of critical importance. If similar, it would suggest that comorbid psychiatric conditions among individuals with ASD are not symptoms of specific, non‐ASD psychiatric disorders per se, but reflect a general liability to psychopathology associated with ASD. To this end, the current study examined whether the higher‐order structure of co‐occurring psychiatric symptoms was the same within ASD and non‐ASD youth. Parents of clinic‐referred youth with ( n = 280) and without ( n = 943) ASD completed a DSM‐IV ‐referenced psychiatric symptom rating scale. A confirmatory factor analytic framework was used to examine four levels of measurement invariance across groups to determine the extent to which transdiagnostic factors were comparable. Transdiagnostic factors were characterized by symptoms of the same disorders (configural invariance) and the same factor loadings across groups (metric invariance). Furthermore, both groups evidenced equivalent numbers of symptoms of most psychiatric conditions with the notable exceptions of attention deficit hyperactivity disorder (ADHD) and social anxiety (partial strong invariance), which were higher in the ASD sample. It was concluded that disparities in the co‐occurrence of psychiatric symptoms between youth with and without ASD may be largely reflective of transdiagnostic factor level differences associated with ASD and not indicative of the ASD diagnosis per se. However, for ADHD and social anxiety, there appears to be some specific associations with the ASD diagnosis. Autism Res 2020, 13: 579–590 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Few transdiagnostic dimensions relate common mental disorder diagnoses with one another. These dimensions explain psychiatric comorbidity (i.e., the finding that many persons possess several disorder diagnoses simultaneously). However, it is unclear if these dimensions differ among children with autism spectrum disorder (ASD), compared with their non‐ASD counterparts. The results of this study demonstrate that underlying transdiagnostic dimensions are similar in both ASD and non‐ASD children. However, there appear to be ASD‐specific differences when it comes to social anxiety and attention deficit hyperactivity disorder.